2017
DOI: 10.1007/s10964-017-0732-2
|View full text |Cite
|
Sign up to set email alerts
|

Gender Norm Salience Across Middle Schools: Contextual Variations in Associations Between Gender Typicality and Socioemotional Distress

Abstract: Youth who feel they do not fit with gender norms frequently experience peer victimization and socioemotional distress. To gauge differences between schools, the current study examined the longitudinal effects of school-level gender norm salience-a within-school association between gender typicality and peer victimization-on socioemotional distress across 26 ethnically diverse middle schools (n = 2607; n = 2805). Boys (but not girls) reporting lower gender typicality experienced more loneliness and social anxie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 47 publications
1
29
0
Order By: Relevance
“…There are other devalued social identities possessed by youth, such as gender atypicality, sexual minority status, or obesity, that also elicit discrimination and that have known consequences not unlike those linked to racial discrimination. Being picked on because you are overweight (e.g., Puhl and Latner, 2007;Schvey et al, 2014) or because you deviate from the gender norms in your school (e.g., Jewell and Brown, 2014;Smith et al, 2018) are also related to mental health and physical health challenges. Yet despite some common consequences, studies on discrimination due to race, gender, or weight have evolved as separate literatures, each examining negative consequences of particular stigmatized social identities in isolation.…”
Section: Study 2: How Presence Of Same-race/ethnicity Peers Shapes Prmentioning
confidence: 99%
“…There are other devalued social identities possessed by youth, such as gender atypicality, sexual minority status, or obesity, that also elicit discrimination and that have known consequences not unlike those linked to racial discrimination. Being picked on because you are overweight (e.g., Puhl and Latner, 2007;Schvey et al, 2014) or because you deviate from the gender norms in your school (e.g., Jewell and Brown, 2014;Smith et al, 2018) are also related to mental health and physical health challenges. Yet despite some common consequences, studies on discrimination due to race, gender, or weight have evolved as separate literatures, each examining negative consequences of particular stigmatized social identities in isolation.…”
Section: Study 2: How Presence Of Same-race/ethnicity Peers Shapes Prmentioning
confidence: 99%
“…Such an approach examining the degree to which a particular individual characteristic (e.g., academic achievement, gender typicality) is associated with social sanctions (positive or negative) within a setting captures norm salience (Cialdini, Kallgren, & Reno, 1991). This method has been applied to study contextual moderator effects across classrooms (Dijkstra & Gest, 2015) and schools (Smith, Schacter, Enders, & Juvonen, 2017). For example, Smith et al (2017) showed that boys who do not perceive themselves as typical of their gender felt more distressed in schools where gender atypicality was more strongly related to perceived peer mistreatment.…”
Section: School-based Weight Normsmentioning
confidence: 99%
“…This method has been applied to study contextual moderator effects across classrooms (Dijkstra & Gest, 2015) and schools (Smith, Schacter, Enders, & Juvonen, 2017). For example, Smith et al (2017) showed that boys who do not perceive themselves as typical of their gender felt more distressed in schools where gender atypicality was more strongly related to perceived peer mistreatment. These contextual effects were documented over and above boys' individual reports of ridicule and exclusion.…”
Section: School-based Weight Normsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1,2] For example, schools with more heteronormative norms have been found to be associated with adverse effects on depressed mood for all boys, i.e., regardless of low or high gender typicality. [3] Gower et al [4] found that schools with more supportive LGBT climates had students reporting lower odds of victimization, regardless of their sexual orientation. Poteat et al [5] showed that victimization had a direct effect on suicide behavior and school belonging, and an indirect effect on educational outcomes (reported grades, truancy, and graduation) for all students regardless of sexuality.…”
Section: Introductionmentioning
confidence: 99%